ANALISIS STUDI KELAYAKAN FINANSIAL PADA USAHA BENGKEL MOBIL & ALAT BERAT (STUDI KASUS: WARTO DIESEL SERVICE INJECTION PUMP – NOZZLE, DI SUMATERA SELATAN) - Putri Samrotul Hidayah; Ihwan Satria Lesmana; Ombi Romli (CV. ALIM'SPUBLISHING, 2024)
The study of financial feasibility is very related and cannot be separated from the business income of the Warto Diesel Service Injection Pump-Nozzle Car and Heavy Equipment Workshop in South Sumatra, it will be more dominant to be assessed whether it is feasible or not can be seen from the financial data during the running time. This study aims to see the financial feasibility of the business through investment appraisal in the Payback Period (PP) method, Accounting Rate of Return (ARR), Net Present Value (NPV), Profitability Index (PI). The research method used in this research is a qualitative method, the data used in this research is Primary data, namely data obtained through direct observation of the Warto Diesel Service Injection Pump-Nozzle Car and Heavy Equipment Workshop business. Data collection techniques are carried out by interview, observation and literature study. The results of research on the Warto Diesel Service Injection Pump-Nozzle Car and Heavy Equipment Workshop business for the last five years are; PP 0,78 years, ARR of 275.98%, NPV of Rp1,707,860,842, PI of 5.269. Based on the overall results of these methods, it shows that the financial feasibility of the Warto Diesel Service Injection Pump-Nozzle Car and Heavy Equipment Workshop business has met the feasibility assessment criteria